HUBUNGAN MOTIF MENONTON DENGAN TINGKAT KEPUASAN SUBSCRIBER SEKUTOMOTIF YOUTUBE CHANNEL GOFAR HILMAN - Ardhi Rimawan Abastian; Mohamad Nuh (Jurnal Komunikasi, 2026)
The presence of the YouTube social media platform can make it easier for audiences to search for and watch a show that someone wants. The motives that each person has until they finally decide to watch a show are very diverse and media is an important need that must be fulfilled to achieve certain satisfaction. One of the public figure's YouTube channels which is quite well known among young Indonesians is Gofar Hilman. On Gofar Hilman's YouTube channel there is a Sekutomotif program which focuses on discussing automotive and modification of cars and motorbikes, engines, accessories, as well as installing spare parts outside and inside cars to motorbikes. With the Sekutomotif broadcast program on the Gofar Hilman YouTube channel, the current research aims to determine the relationship between viewing motives and the level of satisfaction of Sekutamotif subscribers on the Gofar Hilman YouTube Channel in the Fake Motuba Bekasi community. The research uses a descriptive quantitative method with a positivism paradigm, while the data collection technique is carried out using an online survey method via a Google Form link and will be continued by testing the research instrument using the Validity Test and Reliability Test. Meanwhile, the analysis technique used is Pearson Product Moment correlation using IBM SPSS 26 software. The results of this research show a relationship between viewing motives and the level of satisfaction of Sekutamotif subscribers on the Gofar Hilman YouTube Channel in the Fake Motuba Bekasi community.